2002
DOI: 10.1007/s00330-002-1330-5
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler appearance of penile cavernosal–spongiosal communications in patients with severe Peyronie's disease

Abstract: Our objective was to investigate the prevalence and Doppler characteristics of penile cavernosal-spongiosal communications (CSC) in patients with severe Peyronie's disease. These vessels are either anastomoses connecting the cavernosal arteries with the urethral arterial network or afferent vessels to the corpus spongiosum. Twenty patients with severe Peyronie's disease underwent penile color Doppler US after intracavernous injection of prostaglandin E(1). Study inclusion criteria were penile curvature or shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…9 To our knowledge, reverse flow in CSCs has not been reported in the literature. The penis receives its blood supply from the paired internal pudendal arteries.…”
Section: Discussionmentioning
confidence: 81%
“…9 To our knowledge, reverse flow in CSCs has not been reported in the literature. The penis receives its blood supply from the paired internal pudendal arteries.…”
Section: Discussionmentioning
confidence: 81%
“…They also studied the color Doppler appearance of penile CSCs in 20 patients with severe Peyronie disease; 2 of their 20 patients had arteriogenic dysfunction, but none had reversal of flow in the CSCs. 9 We previously described reversed flow in the CSCs in a 57-yearold patient with ED who had late-onset Buerger disease and concluded that reversed flow in the CSCs was a sign of small-artery obstruction. 4 We used the PSV as the reference standard to diagnose arteriogenic impotence.…”
Section: E B Cmentioning
confidence: 94%
“…b Color Doppler US shows venous leak at the level of the scar due to incomplete distension of the erectile tissue presenting with high-velocity venous flows low flow priapism; rarely it can follow high-flow priapism as well [31,37]. During erection the fibrotic plaques may cause penile bending and the involved sinusoids cannot distend causing veno-occlusive dysfunction [4,38].…”
Section: Postraumatic Scarring and Fibrosismentioning
confidence: 98%